Albumin Stabilizes Fibrin Fiber Ultrastructure in Low Serum Albumin Type 2 Diabetes. (2nd May 2013) - Pretorius, Etheresia; Lipinski, Boguslaw; Bester, Janette; Vermeulen, Natasha; Soma, Prashilla
Abstract: Serum albumin is an essential plasma protein that serves an important function in maintaining osmotic pressure. Low levels of this protein are associated with the kidney failure and hemodialysis that are often seen in diabetic patients who are at high risk of thrombotic events. In diabetes, fibrin fiber nets are changed to form dense matted deposits (DMDs, or parafibrin). Here the authors investigate whether parafibrin is also present in diagnosed low-albumin diabetes patients and whether the addition of human albumin to plasma from low-albumin diabetes type 2 individuals may change the architecture of the fibrin nets. The authors show that the addition of albumin to plasma of low-albumin diabetes patients progressively caused the DMDs typically found in these patients to revert back to ultrastructure typically seen in healthy individuals. This disease has an extremely complicated pathophysiology and thus cannot be considered as a simple condition. This study shows that serum albumin levels may play an important role in the structure of fibrin fibrils, making them more susceptible to the fibrinolytic degradation and elimination from the circulation.